Penyuluhan Anti Bullying terhadap Karang Taruna “Bintang Timoer” Dusun Jetak dalam Menciptakan Kondisi Masyarakat yang Harmonis - Sutarto, Retno Eko Mardani; Aisyah Rukmi Widowati; Siti Fatimah; Aziz Widhi Nugroho; Azahery Insan Kamil; Aisyania Yogi Puspita; Siti Nurjanna Lessy; Rengga Kusuma Putra (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Violence and bullying are social issues that still frequently arise among adolescents, both in schools and communities. Lack of knowledge about the forms, impacts, and prevention mechanisms of bullying means that such behavior is often considered normal and not immediately addressed. This community service activity aims to increase the understanding and awareness of adolescents, especially in the Karang Taruna "Bintang Timoer" community in Jetak Hamlet, Pule Village, regarding the importance of bullying prevention through an educational, participatory, and community-based approach. The implementation method includes counseling, interactive discussions, and case simulations that are expected to be able to pioneer positive behavior in the adolescent environment. The results of the activity showed an increase in participants regarding the definition, types, psychological and social impacts of bullying, and prevention strategies. Participants were also able to identify forms of behavior that constitute bullying and develop simple response steps that can be implemented within the youth organization in particular and the community in general. Evaluation through a post-activity questionnaire will show a significant increase in participants' understanding of anti-bullying. This activity is expected to be the first step in building.